2022
DOI: 10.1149/1945-7111/ac6450
|View full text |Cite
|
Sign up to set email alerts
|

Review—Electropolishing of Additive Manufactured Metal Parts

Abstract: Most metal additive manufacturing (AM) technologies are rapidly approaching, and in some cases even exceeding, the Technology Readiness Level 8, indicating that they are widely available and capable of completing a wide range of projects despite identified process restrictions. Thanks to significant technological progress made in the last decade, more industries are incorporating metal AM in their production processes to obtain highly customized parts with complex geometries. However, the poor surface finish o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Previous work has shown that strain relief can be imparted by surface treatment, though this relief is derived from material properties (e.g., porosity, microstructure) which are controlled by the print parameters. 44 Electropolishing Methods EP studies were performed in a BioLogic flat cell reactor, shown in Fig. 3b, which allows the anodecathode distance to be consistently set at 6¢¢ (15.2 cm).…”
Section: Experimental Additively Manufactured 316l Stainless Steel Sa...mentioning
confidence: 99%
“…Previous work has shown that strain relief can be imparted by surface treatment, though this relief is derived from material properties (e.g., porosity, microstructure) which are controlled by the print parameters. 44 Electropolishing Methods EP studies were performed in a BioLogic flat cell reactor, shown in Fig. 3b, which allows the anodecathode distance to be consistently set at 6¢¢ (15.2 cm).…”
Section: Experimental Additively Manufactured 316l Stainless Steel Sa...mentioning
confidence: 99%
“…Mechanical polishing, while effective in certain respects, often falls short in achieving the desired surface quality due to its tendency to ob-scure defects and induce compressive residual stresses. These residual stresses can weaken the material and make it more susceptible to corrosion and other environmental factors, thereby compromising the integrity and durability of metal components [1], [2]. In the early 20th century, significant advancements in surface finishing techniques were achieved through the discovery and development of electropolishing.…”
Section: Introductionmentioning
confidence: 99%
“…The surface layer formed during mechanical processing typically has a deformed structure and deviates from the core metal’s physicochemical properties, often negatively impacting corrosion resistance by increasing the surface electrochemical activity. Electropolishing eliminates this layer, resulting in significantly improved surface characteristics and properties [ 14 , 15 ]. This method does not cause mechanical interaction, damage, or residual stress [ 16 ].…”
Section: Introductionmentioning
confidence: 99%